Massive pleural effusion following high-power and short-duration radiofrequency ablation for treatment of atrial fibrillation: A case report and review of the literature - He, Miaomiao; Qiu, Jie; Bai, Yang; Wang, Yan; Chen, Guangzhi (Frontiers in Cardiovascular Medicine, 2022)
Postpericardial injury syndrome (PPIS) is defined as pericarditis or pericardial effusion that results from recent myocardial infarction or intracardiac interventions. These symptoms typically include fever, leukocytosis, and a high erythrocyte sedimentation rate and elevated C-reactive protein levels. Additionally, pericardial effusion and pleural effusion may be present. It is considered to be a common complication in cardio-surgery with occurrence of 3 to 30 percent. In the last 20 years, a high number of patients with atrial fibrillation suffered from PPIS following radiofrequency catheter ablation. However, previous reports focused on identifying cardiac tamponade and pericardial effusion as its main clinical manifestations. Solitary pulmonary involvement following PPIS with the radiofrequency catheter ablation may occur. We report a case of PPIS that presented pleural effusion as the dominant feature soon after operation and systematic review to illustrate clinical characteristics of PPIS.